Landings of Acetes spp. in the east coast of Sabah in the past 30 years (1990-2019) - Chen, Cheng Ann; C A Belynnda; D K Stephenie; W L Ng; Saleem Mustafa; R Hassan; Rossita Shapawi; Nur Fatihah Abd Halid (2022)
The genus Acetes is a minor planktonic crustacean group, known by locals as ‘Udang Geragau’, ‘Udang Baring’ or ‘Bubok’ in different parts of Malaysia. The main objective of this research is to study the impact of climatic events on Acetes spp. landings at the East Coast of Sabah waters (Kudat and Tawau) in the past 30 years (1990-2019). Landing data on Acetes was obtained from the Fisheries Department of Sabah, Malaysia while the climatic data were provided by Malaysian Meteorological Department. One-way ANOVA analyses were conducted on the mean temperature, relative humidity, rainfall and the annual landings of Acetes spp. Pearson’s correlation test was later performed to measure relationship between the annual Acetes spp. landings and the variables as mentioned above. The results of correlation tests revealed that two variables (mean temperature and relative humidity) were having weak negative correlations with the annual landings in Kudat. Mean annual rainfall showed weak positive correlation with the Acetes landings in Tawau. The present study showed that changes in climatic event does influence the annual landings of Acetes spp. in the East Coast of Sabah.